1998
DOI: 10.1046/j.1365-2036.1998.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of duodenal ulcer healing after 1 week of proton pump inhibitor triple therapy for eradication of Helicobacter pylori

Abstract: The four 1-week treatment regimens were equally effective in healing H. pylori associated duodenal ulcer disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 14 publications
1
19
1
Order By: Relevance
“…Nevertheless, the number of patients included and analysed in each group was comparable to that of previous randomised and published studies. 1,7,11 Although the confidence interval of the difference in healing observed in our study suggests little or no benefit for continued omeprazole treatment after 1 week, on the other hand one cannot exclude the possibility that such treatment increases the healing rate by as much as 13.7%. Larger and adequately powered studies will be needed to definitively address this issue.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…Nevertheless, the number of patients included and analysed in each group was comparable to that of previous randomised and published studies. 1,7,11 Although the confidence interval of the difference in healing observed in our study suggests little or no benefit for continued omeprazole treatment after 1 week, on the other hand one cannot exclude the possibility that such treatment increases the healing rate by as much as 13.7%. Larger and adequately powered studies will be needed to definitively address this issue.…”
Section: Discussioncontrasting
confidence: 59%
“…1 Furthermore, in this study, ulcers were healed in 28 out of 40 patients in whom H. pylori was not eradicated. 1 In another study, with a design similar to ours, all 52 patients had an ulcer, which was healed by 28 days, where the H. pylori cure rate was 96%. 2 In our study, as for other studies, the percentage of patients with healed ulcer was no different whether H. pylori was eradicated or not.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Twenty‐two studies fulfilled the inclusion criteria and contained data for at least one of the planned comparisons. For the main comparison, 18 studies reported ITT analysis and 20 PP analysis 8 –29 . Detailed characteristics of the studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%